2021
DOI: 10.1038/s41593-021-00926-1
|View full text |Cite
|
Sign up to set email alerts
|

The SARS-CoV-2 main protease Mpro causes microvascular brain pathology by cleaving NEMO in brain endothelial cells

Abstract: Coronavirus disease 2019 (COVID-19) can damage cerebral small vessels and cause neurological symptoms. Here we describe structural changes in cerebral small vessels of patients with COVID-19 and elucidate potential mechanisms underlying the vascular pathology. In brains of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-infected individuals and animal models, we found an increased number of empty basement membrane tubes, so-called string vessels representing remnants of lost capillaries. We obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
200
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(231 citation statements)
references
References 84 publications
(154 reference statements)
15
200
1
1
Order By: Relevance
“…Consistent with this, the receptors involved in SARS-CoV-2 infection including ACE2 were seen to be expressed in the cells of the neurovascular unit, especially in astrocytes and microglial cells (Torices et al, 2021). Recent studies also showed that human pericyte-like cells from brain organoids and endothelial cells from mouse cerebral microvessels can be infected by SARS-CoV-2 (Wang et al, 2021;Wenzel et al, 2021). Interestingly, it was verified that ACE2 was predominantly localized in the pericytes from the mouse microvessels (Wenzel et al, 2021).…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Consistent with this, the receptors involved in SARS-CoV-2 infection including ACE2 were seen to be expressed in the cells of the neurovascular unit, especially in astrocytes and microglial cells (Torices et al, 2021). Recent studies also showed that human pericyte-like cells from brain organoids and endothelial cells from mouse cerebral microvessels can be infected by SARS-CoV-2 (Wang et al, 2021;Wenzel et al, 2021). Interestingly, it was verified that ACE2 was predominantly localized in the pericytes from the mouse microvessels (Wenzel et al, 2021).…”
Section: Introductionsupporting
confidence: 53%
“…Recent studies also showed that human pericyte-like cells from brain organoids and endothelial cells from mouse cerebral microvessels can be infected by SARS-CoV-2 (Wang et al, 2021;Wenzel et al, 2021). Interestingly, it was verified that ACE2 was predominantly localized in the pericytes from the mouse microvessels (Wenzel et al, 2021). Further studies showed that SARS-CoV-2 is able to directly infect neural stem cell-derived astrocytes (Crunfli et al, 2020) and hamster astrocytes (de Oliveira et al, 2021), and that SARS-CoV-2 spike protein was present in different cells from brain of patients, the majority of these cells being astrocytes (Crunfli et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A more straightforward mechanism that might explain the link between the fast changes in OB volume that olfactory training is known to induce is potential changes in the OBs vascularization. Recent data suggest that nearly all individuals infected by the SARS-CoV-2 virus, regardless of whether symptomatic or not, experience endothelial cell death which cause microvascular damage to tissue along the olfactory pathway (Meinhardt et al, 2021;Wenzel et al, 2021). Given the flexibility of the OBs vascularization and close link to amount of olfactory input (Korol & Brunjes, 1992), this suggest that olfactory training might help alleviate OB morphological loss due to COVD-19.…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported, fatigue, headache and “brain fog” are undoubtedly the most common symptoms of long COVID, with an estimated prevalence 58%, 44%, and 27% prevalence 5 , 14 , 29 , 42 . Fatigue is more than a mere state of tiredness: it is a persistent state of weariness taking a heavy toll on physical and mental energy, often reported by patients for several weeks following the acute phase of COVID-19, independently of the severity of the disease 5 , 14 , 29 , 43 .…”
Section: Resultsmentioning
confidence: 54%
“…As SARS-CoV-2 has been identified in the cerebrospinal fluid 40 , 41 , encephalitis following direct viral neuronal damage has been included among the complications of COVID-19. SARS-CoV-2 has also been proven able to infect brain endothelial cells, resulting in microvascular pathology occurring in brain vessels which can also influence the blood-brain barrier 42 .…”
Section: Resultsmentioning
confidence: 99%